The idea of a modified dialectics and philosophy in Theodor W. Adorno’s thought - Fallas-Vargas, Fabrizio (Revista de Filosofía, 2022)
This paper explores some of the relations between dialectics and philosophy within Adorno’s program of a modified dialectics. How to think about the tension between dialectical categories and philosophy through the prism of negative dialectics? What does it mean, from Adorno’s thought, to liberate the philosophy and dialectics of their affirmative character? Elaborating these questions is the target of this work.